2019
DOI: 10.3390/ijerph16224348
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality in Istanbul during Extreme Heat Waves between 2013 and 2017

Abstract: Heat waves are one of the most common direct impacts of anthropogenic climate change and excess mortality their most apparent impact. While Turkey has experienced an increase in heat wave episodes between 1971 and 2016, no epidemiological studies have examined their potential impacts on public health so far. In this study excess mortality in Istanbul attributable to extreme heat wave episodes between 2013 and 2017 is presented. Total excess deaths were calculated using mortality rates across different categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…In India, cold temperatures below 13.8°C were associated with increased risk of 6.3% for all-cause mortality, 27.2% for stroke mortality, 9.7% for ischemic heart disease mortality, and 6.5% for respiratory diseases mortality [ 92 ]. In Istanbul-Turkey, 23 days of exposure to hot temperature above 22.8°C was associated with a total of 419 excess deaths [ 90 ]. In Korea, hot temperature days of 25°C compared to 15°C were significantly associated with a 4.5% increase in cardiovascular hospitalizations [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…In India, cold temperatures below 13.8°C were associated with increased risk of 6.3% for all-cause mortality, 27.2% for stroke mortality, 9.7% for ischemic heart disease mortality, and 6.5% for respiratory diseases mortality [ 92 ]. In Istanbul-Turkey, 23 days of exposure to hot temperature above 22.8°C was associated with a total of 419 excess deaths [ 90 ]. In Korea, hot temperature days of 25°C compared to 15°C were significantly associated with a 4.5% increase in cardiovascular hospitalizations [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies from different countries have found environmental aspects that are key factors attributable to human mortality [1][2][3][4]. Extreme climates occur more frequently than ever due to global warming, encouraging more research on the impact of temperature variations on health outcomes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Unless prepared for and mitigated, extreme temperatures can have detrimental health impacts, including excess mortality, even among communities that are accustomed to recurring heat waves ( 7 , 8 ). In the past two decades, heat waves caused excess mortality in many countries, ranging from an increase of 38% ( 7 , 9 , 10 ) to more than 135% ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sustained heat waves pose a substantial risk for vulnerable populations, including the elderly, young children, individuals that suffer from respiratory or cardiovascular diseases, as well as tourists or migrants that are not accustomed to similar weather conditions or cannot understand heat wave warnings due to language barriers ( 1 , 13 ). When exposed to extreme temperature environments to which they are not physically accustomed, vulnerable populations become more susceptible to morbidity and even death ( 8 , 14 ). Beyond physical morbidity and mortality, heat waves are also reported for their potentially severe impact on “mental health and societal wellbeing” ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation